Oxygen functional groups in graphitic carbon nitride for enhanced photocatalysis - Liu, S.; Li, D.; Sun, Hongqi; Ang, Ming; Tadé, Moses; Wang, Shaobin (2016)
© 2016 Elsevier Inc. Metal-free semiconductors offer a new opportunity for environmental photocatalysis toward a potential breakthrough in high photo efficiency with complete prevention of metal leaching. In this study, graphitic carbon nitride (GCN) modified by oxygen functional groups was synthesized by a hydrothermal treatment of pristine GCN at different temperatures with H2O2. Insights into the emerging characteristics of the modified GCN in photocatalysis were obtained by determining the optical properties, band structure, electrochemical activity and pollutant degradation efficiency. It was found that the introduction of GCN with oxygen functional groups can enhance light absorption and accelerate electron transfer so as to improve the photocatalytic reaction efficiency. The photoinduced reactive radicals and the associated photodegradation were investigated by in situ electron paramagnetic resonance (EPR). The reactive radicals, O2 - and OH, were responsible for organic degradation.